Pregnancy and neurodevelopmental outcomes with in-utero antiepileptic agent exposure. A pilot study. (January 2015) - Arkilo, Dimitrios; Hanna, Julie; Dickens, Deanna; Justesen, Lorna; Brunn, Jenny; Garland, Sarah; Penovich, Patricia
Abstract Objective To assess pregnancy outcomes on women exposed to monotherapy with antiepileptic agents. Methods Questionnaires were sent to women with epilepsy in our practice who were pregnant between 2006 and 2011. 62/86 patients (72%) who responded were on monotherapy. 24 fetuses (63%) were exposed to lamotrigine, 11 (28%) to levetiracetam, 2 (5.2%) to topiramate, 1 (2.6%) to gabapentin, 17 (27%) to carbamazepine, 5 to phenytoin and 2 to valproate. Results There were 55 (88%) live births and 7 unsuccessful pregnancies (miscarriages/stillbirths). Unsuccessful pregnancies were reported in 2/24 gestations exposed to lamotrigine, 2/11 to levetiracetam and 3/17 to carbamazepine. Delayed motor development or speech delay requiring therapy and special programming was noted in 2/24 children prenatally exposed to lamotrigine, 3/17 exposed to carbamazepine and 1/2 children exposed to valproate. Conclusion Our pilot study of children exposed to antiepileptic drug monotherapy in-utero demonstrated a favorable trend for successful pregnancy outcomes and developmental trajectory.